2003
DOI: 10.1097/01.sap.0000054731.37252.f9
|View full text |Cite
|
Sign up to set email alerts
|

Double V-Y Advancement Flap in the Management of Lower Lip Reconstruction

Abstract: A new method for lower lip reconstruction is proposed. It is based on a double cutaneous and mucous V-Y advancement flap and is suggested for the surgical treatment of lip cancer confined between the skin and the vermilion with a horizontal spread. Sixteen patients were treated from 1996 to 2001 with this technique and the results were satisfactory both from the functional and the aesthetic standpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…The repair that we used, being a combination of 2 island pedicle or V-Y flaps, has been previously described. [1][2][3][4][5][6][7] Our technique differs slightly from previous descriptions in the use of the setback pexing suture from the undersurface of the flap to the base of the defect and the description of trimming the flaps to recreate the vermilion border at the Cupid's bow. This pexing suture, along with everting buried sutures, is very helpful in preventing trapdooring.…”
Section: Discussionmentioning
confidence: 98%
“…The repair that we used, being a combination of 2 island pedicle or V-Y flaps, has been previously described. [1][2][3][4][5][6][7] Our technique differs slightly from previous descriptions in the use of the setback pexing suture from the undersurface of the flap to the base of the defect and the description of trimming the flaps to recreate the vermilion border at the Cupid's bow. This pexing suture, along with everting buried sutures, is very helpful in preventing trapdooring.…”
Section: Discussionmentioning
confidence: 98%
“…Bocchi et al mentioned that the maximum height of defects that they can reconstruct using their method is 1.5 cm [5].…”
Section: Discussionmentioning
confidence: 99%
“…Bayramiçli et al [4] reported an orbicularis oris musculocutaneous flap that preserved the mental nerve. Bocchi et al [5] made two V-Y advancement flaps on the skin side and the mucosal side. Yano et al [6] used V-Y advancement flaps with a tongue flap, which is used for the red lips.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations